Determinants of efficiency in child care provision - Anna Montén; Christian Thater (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2010)
This article analyzes the efficiency in the provision of child care services at the municipal level and identifies the main determinants of inefficiency. We use a unique data set on the local child care expenditures in the eastern German State of Saxony. The analysis is performed in two stages. First, we measure the efficiency by using a Data Envelopment Analysis (DEA). Second, we consider political, fiscal and demographic variables in a truncated regression to identify the determinants of inefficiency. We find substantial differences in efficiency; the median municipality is up to 28% inefficient in expenditures on child care. Explanatory variables such as an uncompensated mayor or a larger share of over 65-year olds significantly increases inefficiency.
Keywords: H42; H72; J13; 330; Child care; efficiency analysis; municipalities; service provision; Kommunale Ausgaben; Kinderbetreuungseinrichtung; Wirtschaftliche Effizienz; Data-Envelopment-Analyse; Kommunalverwaltung; Sachsen